Dynamic stock, flow, and emissions of brominated flame retardants for vehicles in Japan. (20th September 2019) - Liu, Heping; Yano, Junya; Kajiwara, Natsuko; Sakai, Shin-ichi
Abstract: The transportation industry, including the automobile industry, is one of the primary manufacturing sectors that have used polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCD) within interior components. In this study, a dynamic substance flow model and scenario analysis were used to analyze the trends of PBDE and HBCD stocks, and the flow and emissions from vehicles were estimated. Under the strict elimination scenario, the average amount of commercially decabrominated diphenyl ether (c-DecaBDE) was 62 ± 21 g per conventional passenger vehicle (CPV) and 38 ± 13 g per miniature passenger vehicle (Mini PV). The average amount of HBCD was 3 ± 2 g per CPV and 2 ± 1 g per Mini PV. Seat fabric contributed ∼87% of the c-DecaBDE, while floor covering contributed ∼73% of the HBCD for passenger vehicles (PVs). For vehicles in use, the amount of c-DecaBDE was ∼2800–3100 tonnes from fiscal year 1998 (FY1998), while that of HBCD was ∼120–130 tonnes from FY2002; this remained stable until elimination began. Scenario analysis revealed that at least 5000–6700 tonnes of c-DecaBDE and 260–280 tonnes of HBCD entered in domestic PVs use could be avoided through elimination measures taken by Japanese vehicle manufacturers. The flows of c-DecaBDE and HBCD in FY2003 and FY2013 also demonstrated the effectiveness of elimination measures. However, approximately 300 ± 100 tonnes of c-DecaBDE and 1.8 ± 1.1 tonnes of HBCD will still be stocked in vehicles in FY2030. The atmosphere is the main environmental media for c-DecaBDE and HBCD emissions, and the usage phase is the most important stage. The fate of brominated flame retardants (BFRs) during and after material recycling should be carefully monitored and managed because the end-of-life vehicle treatment stage may become the dominant phase of BFR emissions with the decline of c-DecaBDE and HBCD stocked in vehicles. Graphical abstract: Image 1 Highlights: Dynamic SFA and scenario analysis of c-DecaBDE and HBCD in vehicles were estimated. Seat fabric detected with PBDEs originated from c-DecaBDE 45, 000 ± 15, 000 mg/kg. C-DecaBDE in-use vehicles stably ranged at ∼2800–3100 t and HBCD at ∼120–130 t. Elimination measures could cumulatively avoid 5000–6700 t c-DecaBDE by 2040. Thermal recover of ASR decomposes >78% of c-DecaBDE to atmosphere in ELV in FY2040.